The Role Of Parents In Character Education During The Covid-19 Pandemic In The Perspective Of The Qur’an And Hadith - Dinny Pertiwi Dewi; Ainun Nadlif (ISTAWA, 2021)
The presence of the Covid-19 pandemic in Indonesia has changed almost all aspects of life, one of them being the aspect of education. With the help of technology, the teaching process is done online from the home of each student. The role of parents, in this case, is very much needed in educating children for the formation of characters that are not obtained in the school environment. This article aims to determine the role of parents in shaping the character of their children during the Covid-19 pandemic through the perspective of the Qur'an and Hadith. By using a descriptive qualitative research method, the implementation of the research is carried out by field observation. The conclusion of this research is that role of parents is important in shaping the character of their children n to become better children, as an educator, facilitators, motivators, and role models for the child (Al-Uswah Al-Hashanah).